Analysis of the Influence of Workload-Based Staff Requirements on the Outpatients Coding Section of BPJS with WISN Method - Hutasoit, Theresia; Devi Fitriani, Arifah; Begum Suroyo, Razia (Hasanuddin Medan, 2023)
Professional staffs in the coding section have an important role in doing activities in the hospital. The coding section officer is responsible for documents claimed by BPJS Health and is responsible for the claim. This study aims to determine the estimated number of workers in the outpatients coding section of BPJS needed based on the WISN (Workload Indicator Staff Need) method and to determine the competence and workload of coding officers. This is qualitative research using work time and measurements the WISN (Workload Indicator Staff Need) method. Retrieval of data from this study used observations, interviews and documentation studies. The results of this study were in the form of an estimate of the number of outpatient coding officers for BPJS patients needed to do job descriptions properly so that maximum work results were achieved. The results of the workload calculation using the WISN (Workload Indicator Staff Need) method, the minimum number of workers required was two officers, where currently there were two outpatient coding officers, so it was advisable to add two people, including one doctor as verification and one more person scanning the medical record. These additions should consider the competence of personnel in their fields so that they are able to perform well in accordance with existing standards.